التفكير السياسي لعمرو خليفة النامي قراءة في "كلمات للثورة" أنموذجًا" - إبراهيم خالد علي (Sharwes Scientific Journal, 2024)
This study examines the thinking tools employed by Amr Khalifa Al-Nami politically in his article "Words for the Revolution," through referencing, methodology, presentation mechanisms, and the impacts of this article. It seeks to review his political arguments and demonstrate his approach to politics and the framework he relies on. The significance of this study lies in highlighting the contributions of scholars from “Jabal Nafusa” in political guidance, attempting to articulate a hypothesis of a political framework from which broad outlines can be drawn to achieve a state characterized by rational cultural political activity. Al-Nami was one of those who conceived political solutions for Libya through his article "Words for the Revolution," giving us insight into this experience which was met with denial, imprisonment, and marginalization. The primary problem lies in why Amr Khalifa Al-Nami? Despite not engaging in politics, this is the main axis. Then gradually comes the article "Words for the Revolution": What is its reference? What is its methodology? And its presentation mechanisms. Study objectives: This study aims to reach a conclusion that clarifies the path taken by Al-Nami in "Words for the Revolution" and highlights the foundations he relied on in its presentation and guidance